PENGARUH MODAL, JAM KERJA, DAN PENGGUNAAN OJEK ONLINE TERHADAP PENDAPATAN USAHA BIDANG KULINER DI KOTA DENPASAR - Arlista, Ida Ayu Agung Nindya; Utama, Made Suyana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.10.TAHUN.2022DO - 10.24843/EEB.2022.v11.i10.p05, 2022)
The MSME sector became the backbone of the economy during the pandemic that swept across the world, causing many people to lose their jobs so that urban communities chose the trade sector as a way of survival. Culinary business is a business that is easy to run because the capital required is relatively small and does not need a higher education background. Along with the development of technology and people's lifestyles, entrepreneurs are required to always innovate so as not to be out of date. This study aims to analyze the simultaneous and partial effect of capital, working hours, and the use of online motorcycle taxis on business income in the culinary sector in Denpasar City. The research sample is MSMEs in the culinary field in Denpasar City with a total sample of 99 obtained using a non-probability sampling method, namely accidental sampling. The data analysis technique used in this study is multiple linear regression analysis with data collection methods using questionnaires. The results of the analysis found that simultaneously and partially the variables of capital, working hours, and the use of online motorcycle taxis had an effect on business income in the culinary field in Denpasar City..